2022
DOI: 10.1002/jtr.2511
|View full text |Cite
|
Sign up to set email alerts
|

Perceived organizational support and well‐being of tour guides: The mediating effects of quality of work life

Abstract: The reciprocity norm theory suggests that individuals develop a sense of obligation and indebtedness to reciprocate the favorable treatment they receive. Rooted in the notion of reciprocity norm, organizational support is regarded as essential for organizations to maintain long-term relationships with their employees. Despite an established academic discussion on organizational support and its outcomes in behavioral and applied psychology research, a comprehensive understanding of its role in enhancing employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
0
1
0
Order By: Relevance
“…Specifically, some studies have shown that POS significantly affects employee wellbeing (Roemer & Harris, 2018;Wattoo et al, 2018). Likewise, POS enhances employees' quality of work life and lessens burnout and stress (Altinoz, Cop, Cakiroglu, & Altinoz, 2016;Demirdelen Alrawadieh & Alrawadieh, 2022). This argument is in line with Aselage and Eisenberger (2003) findings that when employees are treated properly, their level of POS increases, improving their employee wellbeing.…”
Section: The Influence Of Perceived Organisation Support On Workplace...mentioning
confidence: 66%
See 1 more Smart Citation
“…Specifically, some studies have shown that POS significantly affects employee wellbeing (Roemer & Harris, 2018;Wattoo et al, 2018). Likewise, POS enhances employees' quality of work life and lessens burnout and stress (Altinoz, Cop, Cakiroglu, & Altinoz, 2016;Demirdelen Alrawadieh & Alrawadieh, 2022). This argument is in line with Aselage and Eisenberger (2003) findings that when employees are treated properly, their level of POS increases, improving their employee wellbeing.…”
Section: The Influence Of Perceived Organisation Support On Workplace...mentioning
confidence: 66%
“…Studies indicate that TRL significantly influences perceived organisational support (Stinglhamber, Marique, Caesens, Hanin, & De Zanet, 2015;Suifan et al, 2018). Similarly, POS significantly influences employee wellbeing (Demirdelen Alrawadieh & Alrawadieh, 2022;Roemer & Harris, 2018;Wattoo, Zhao, & Xi, 2018). So, the influence of transformational leadership on employee wellbeing is assumed to be mediated by POS.…”
Section: Introductionmentioning
confidence: 99%
“…In the future, other researchers could use personality trait theory to consider the specific role of personality traits of supervisors or employees on employees' work meaningfulness. Moreover, psychological perceptions, for example, employees' sense of organizational support, equally contribute to positive work behavior and perceived work value (Alrawadieh and Alrawadieh 2022). Therefore, we encourage subsequent researchers to explore the complex mechanism of supervisor developmental feedback on employees' work meaningfulness from the perspective of other psychological perceptions systematically.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Employees who perceive higher levels of organizational support report higher levels of job satisfaction and demonstrate higher levels of performance (Cullen et al, 2014). Several studies have investigated the relationship between POS with job satisfaction (Alrawadieh and Alrawadieh, 2022;Ayuningtias et al, 2019;Eisenberger et al, 1997;Kurtessis et al, 2017;Maan et al, 2020;Riggle et al, 2009;Rhoades and Eisenberger, 2002;Yakut and Erg€ un, 2022). These studies concluded that POS and job satisfaction are positively associated.…”
Section: Conceptual Relationships and Statement Of Hypothesesmentioning
confidence: 99%
“…, 2014). Several studies have investigated the relationship between POS with job satisfaction (Alrawadieh and Alrawadieh, 2022; Ayuningtias et al. , 2019; Eisenberger et al.…”
Section: Literature Reviewmentioning
confidence: 99%